Suspension system optimisation to reduce whole body vibration exposure on an articulated dump truck - Kirstein, Johannes Cornelis (Stellenbosch : University of Stellenbosch, 2006)
Thesis (MScEng (Mechanical and Mechatronic Engineering))--University of Stellenbosch, 2005.